SYNTHESIS AND CHARACTERISATION OF Fe₃O₄-SnO₂ NANOCOMPOSITES WITH ELECTROCHEMICAL PROPERTIES - MACAVEI, Sergiu; ȘTEFAN, Maria; POGĂCEAN, Florina; PANĂ, Ovidiu; LEOŞTEAN, Cristian; POPA, Adriana; TOLOMAN, Dana; BARBU-TUDORAN, Lucian (Studia Universitatis Babeș-Bolyai Chemia, 2020)
Composite Fe₃O₄-SnO₂ nanoparticles were synthesized by growing SnO₂ nanoparticles on the surface of previously prepared Fe₃O₄ nanoparticles. First, Fe₃O₄ nanoparticles were prepared by chemical precipitation of precursors followed by the obtaining of SnO₂ nanoparticles by chemical precipitation or sol-gel process. The composite nanoparticle samples were characterized by using X-Ray diffraction (XRD), Transmission Electron Microscopy (TEM) and X-Ray photoelectron Spectroscopy (XPS) techniques. Also, electrochemical behaviour was recorded. The results revealed that by adjusting the composition of components one can control the properties of composite nanoparticles.